5G new radio design:why/how to extend/innovate from LTE - Hui TONG (Dianxin kexue)
Driven by the 5G visions including “wireless infrastructure to connect the world”, ITU has defined the three main usage scenarios of 5G: eMBB, mMTC, and uRLLC, and the consequent requirements (performance metrics) are defined as well. Then, 3GPP completed technical studies and standards towards satisfying ITU requirements, namely 5G new radio (NR). Two essential aspects of 5G NR were discussed. Firstly, why can 5G NR reuse the basic technology of 4G LTE was discussed, i. e. , how does the MIMO-OFDM framework satisfy ITU 5G requirements. Secondly, what innovations had been done in 5G NR, comparing with LTE, including some details on the four new features of 5G NR, namely “new architecture, new design, new bands, new antenna”. The future technology trends were briefly introduced in the conclusion section.